Desenvolvimento de uma ferramenta computacional experimental para navegação em sites web para cegos - Ganança, Alexandre Sobrino (2010)
Although it seems plausible to consider the importance of the Internet as an educational and/or professional tool for people with special needs, several studies support the idea that the increasing web page complexity renders access to information ever so much more difficult for the visually impaired. Based on the analysis of the resources available in some of the most popular commercial and free products, and on some of the major difficulties this group of users faces, this dissertation proposes an experimental computational tool to support screen reader software aiming to improve the browsing experience for the visually impaired by implementing a set of mechanisms designed to simplify the way such users can reach the textual information itself. Presented and submitted to the assessment of a group of volunteer users, it was possible to observe that the proposed application, despite its limitations, helped to enhance the browsing experience by visually impaired users, reducing the effort required to get to the content that was being searched for. Additional notes provided by the participants by means of evaluation forms, in addition to other observations derived from the monitoring of the browsing sessions, allow us to conclude that improvements, corrections and further implementations can draw the tool even closer to the expectations of its potential users.